Effect of preoperative cannabis use on perioperative outcomes: a retrospective cohort study. Issue 8 (14th May 2021) - Zhang, Betty Huiyu; Saud, Haris; Sengupta, Neil; Chen, Max; Bakshi, Devyani; Richardson, Liz; Wang, Li; Shanthanna, Harsha
Abstract : Introduction: The reported use of cannabis within surgical population is increasing. Cannabis use is potentially associated with increased harms and varied effects on pain control. These have important implications to perioperative care. Methods: We conducted a retrospective cohort study comparing surgical patients reporting cannabis use preoperatively to control patients with no cannabis exposure, in a 1:2 ratio. To control for confounding, we used a propensity score-matched analysis to assess the adjusted association between cannabis use and study outcomes. Our primary outcome was a composite of (1) respiratory arrest or cardiac arrest, (2) intensive care admission, (3) stroke, (4) myocardial infarction and (5) mortality during this hospital stay. Secondarily, we assessed the effects on pain control, opioid usage, induction agent dose and nausea-vomiting. Results: Between January 2018 and March 2019, we captured 1818 patients consisting of cannabis users (606) and controls (1212). For propensity score-matched analyses, 524 cannabis patients were compared with 1152 control patients. No difference in the incidence of composite outcome was observed (OR 1.06, 95% CI 0.23 to 3.98). Although a higher incidence of arrhythmias (2.7% vs 1.6%) and decreased incidence of nausea-vomiting needing treatment (9.6% vs 12.6%) was observed with cannabis users vs controls, results were not statistically significant. No significant differences were observed with other secondary outcomes. Conclusion: Our results do not demonstrate a convincing association between self-reported cannabis use and major surgical outcomes or pain management. Perioperative decisions should be made based on considerations of dose, duration, and indication.